2019
DOI: 10.5222/head.2019.033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nurses’ Views about Hand Washing Habits and Hand Hygiene Compliance Rates

Abstract: Aim: This descriptive and observational study was conducted to identify the opinions of nurses regarding hand washing habits and to assess their hand hygiene compliance rates. Methods: The nurses (n=63) were asked about their views regarding their hand hygiene habits. Nurses' hand hygiene compliance and hand washing behaviors were observed. Nurses were not aware that their hand washing behaviors were observed. Hand washing behaviors were assessed using the Hand-washing Observation Tool. Results: Nurses reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
5
0
4
Order By: Relevance
“…This result proved that an increase in the hand hygiene beliefs of nursing students would affect their hand hygiene practices in a positive direction. There are similar studies in the literature where the positive relationship between hand hygiene beliefs and practices was discussed [5,6,21,25]. Nevertheless, it is believed that this study will contribute to the literature in terms of structurally testing the relationship between hand hygiene beliefs and hand hygiene practices.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This result proved that an increase in the hand hygiene beliefs of nursing students would affect their hand hygiene practices in a positive direction. There are similar studies in the literature where the positive relationship between hand hygiene beliefs and practices was discussed [5,6,21,25]. Nevertheless, it is believed that this study will contribute to the literature in terms of structurally testing the relationship between hand hygiene beliefs and hand hygiene practices.…”
Section: Discussionmentioning
confidence: 51%
“…Although it is emphasized in the literature that hand washing is the most important procedure alone in preventing infections, it is known that nurses' compliance with handwashing protocols is insufficient [1,[3][4][5]. Studies on this issue report that nurses' incompatibility with handwashing depends on several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…27 Bu çalışmada; katılımcıların EH'nin gerekliliğine olan inanç düzeylerinin yüksek olduğu, bu durumun Türkiye'de ve yurt dışında yapılan çalışmalarla uyumluluk gösterdiği belirlenmiştir. 4,21,[28][29][30] El yıkamanın temelinde; ellerin temiz su ve sabunla yıkanması gelmektedir. Soğuk veya sıcak su ciltte kuruluğa neden olabileceği için ılık su, temizleyici olarak da antimikrobiyal, normal veya sıvı sabun tercih edilebilir.…”
Section: Discussionunclassified
“…The present study determined that in the first stage of the COVID-19 pandemic, the most frequently used hand hygiene material within the last three months was alcohol-based hand disinfectant along with water and soap by 62.9%. In the study by Karaoğlu and Akın (2019), the most frequently used material for hand hygiene by nurses was alcohol-based hand disinfectant besides water and soap, with a rate of 81.6%. In another study conducted by Toraman et al (2009) within the intensive care unit of a private hospital, 1397 occasions in total that require hand washing were identified.…”
Section: Fear Of Covidmentioning
confidence: 99%
“…In the observational research conducted by Karaoğlu and Akın (2019), 21% of handwashing processes took less than 5 seconds, 73.2% took 5-15 seconds, 5.8% took longer than 15 seconds, and 77.8% of the nurses dried their hands after the handwashing process. In this research, the rate of those who reported handwashing to take between 15-30 seconds was 75.3%, and that of those drying their hands with a paper towel after handwashing was 93.8%.…”
Section: Fear Of Covidmentioning
confidence: 99%